The more engaging, the more enjoyable? Age matters in predicting perceived enjoyment with different Facebook activities - Zhang, Lianshan; Jung, Eun Hwa (Frontiers in Psychology, 2022)
Drawing upon uses and gratifications perspectives and socioemotional selectivity theory, this study examined the differences in the use of Facebook features among younger, middle-aged, and older adults. Furthermore, it explored the association between Facebook activities and users’ perceived enjoyment for different age groups. An online survey was conducted with 647 Facebook users in the US. An exploratory factor analysis identified four types of Facebook activities: broadcasting, directed communication, content consumption, and information regulation. The results revealed that younger users’ broadcasting, content consumption, and information regulation activities substantially differed from those of older users. In addition, broadcasting and content consumption activities were more popular among younger users and more predictive of younger users’ enjoyment. Directed communication was more powerful in predicting middle-aged and older users’ enjoyment. However, younger and middle-aged users’ engagement with information regulation activities was negatively related to their enjoyment on Facebook. The study findings provide more nuanced knowledge regarding user experiences on social networking sites (SNSs) among specified age groups and practical insights into the improvement of SNSs by addressing their different needs.